Islam as an Ideology: The Political Thought of Tjokroaminoto - Hasnul Arifin Melayu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
There are two reasons why Tjokroaminoto maintained a cooperative attitude toward the Dutch. First, he was more inspired by the fear of government retaliation than by conviction; at that time, based on Article 111 of the ordinance of 1854, the Dutch government forbade any political association. Second, this attitude could not be separated from the political environment created by the Dutch government. A moderate attitude shown by Governor General Idenburg created a sympathetic attitude among the S.I. leaders toward the Dutch.DOI: 10.15408/sdi.v9i3.659